Ultrasensitive Identification of Localization Variants of Modified Peptides Using Ion Mobility Spectrometry - Ibrahim, Yehia M. (2011)
Localization of the modification sites on peptides is challenging, particularly when multiple modifications or mixtures of localization isomers (variants) are involved. Such variants commonly coelute in liquid chromatography and may be undistinguishable in tandem mass spectrometry (MS/MS) for lack of unique fragments. Here, we have resolved the variants of singly and doubly phosphorylated peptides employing drift tube ion mobility spectrometry (IMS) coupled to time-of-flight mass spectrometry. Even with a moderate IMS resolving power of ~80, substantial separation was achieved for both 2+ and 3+ ions normally generated by electrospray ionization, including for the variant indistinguishable by MS/MS. Variants often exhibit a distribution of 3-D conformers, which can be adjusted for optimum IMS separation by prior field heating of ions in a funnel trap. The peak assignments were confirmed using MS/MS after IMS separation, but known species could be identified using just the ion mobility ‘tag”. Avoiding the MS/MS step lowers the detection limit of localization variants to <100 attomoles, an order of magnitude better than that provided by electron transfer dissociation in an Orbitrap MS.